La concurrence discursive - Karine Collette (Communication)
We approach written communication between public administration and the users through discourse from three spaces where meaning is constructed through the written word : conception discourses, made by professional editors, the discourses of text, materialised in mailings, and the discourses of users which actualize the mailings that they interpret. The analysis of this sample allows us to extract the socio-cognitive logics which lie beneath the discourses of production and of reception as well as the logic of the texts. The gaps between these logics of conception, materialization, and actualization describe major dysfunctions and reveal an original distribution of the social and linguistic competencies connected to the activities of the production-reception of texts.